Reconstruction of the 29th December 2013 eruption of San Miguel volcano, El Salvador, using video, photographs, and pyroclastic deposits - Brown, Richard James; Hernández, Walter; Escobar, Demetrio; Gutierrez, Eduardo; Crummy, Julia; Cole, Rosemary; Tournigand, Pierre-Yves (Volcanica, 2022)
San Miguel (or Chaparrastique) volcano, El Salvador, erupted on the 29th December 2013, after almost 40 years of quiescence. Initial vent-clearing explosions ejected ballistic blocks and produced a pyroclastic density current (PDC) that flowed down the upper flanks. Plume rise speeds peaked at 50–70 m s-1 and declined over time. The main phase of the VEI 2 eruption produced a Subplinian plume that dispersed 106 m3 ash >20 000 km2 across El Salvador in to Honduras. Plume structure was complex due to strong wind shear and to contributions from co-PDC ash. Tephra fall deposits dispersed westwards include a basal white ash layer of ash-coated clasts and ash aggregates, a grey fine ash co-PDC layer, and a layer of coarse ash to fine lapilli-grade scoria. The eruption provides a useful case study to understand the range of volcanic activity at the volcano and to refine hazard maps.